The role of brand image as an intervening variable to increase purchase decisions - Yusup, Ariska Maulana; Lukitaningsih, Ambar; Fadhilah, Muinah (Manajemen dan Bisnis, 2025)
Intensifying competition in Indonesia’s food & beverage industry forces brands to differentiate. This study analyses whether brand image mediates the influence of store atmosphere and celebrity endorsement on purchase decisions in coffee shops. Data from 144 customers were gathered through purposive sampling and analysed with SPSS 23, employing validity, reliability, classical assumption, and Sobel tests. Results confirm that store atmosphere and celebrity endorsement positively affect both brand image and purchase decisions. Brand image is also proven to fully mediate the relationship between store atmosphere and purchase decisions, resolving inconsistencies in previous studies and providing practical guidance for coffee‐chain marketers.